Natural gross radioactivity in various surface and tap waters in Elazig, Turkey - Dogru, M; Canbazoglu, C (Kluwer Academic Publ, 2002)
Gross-alpha and gross-beta activities of fourteen taps and wells, four lakes and three drinking water supplies in Elazig (Turkey) were determined. The results obtained indicate that although the natural radioactivity of six tap, two drinking, four lake and three well water samples does not exceed the requirements of the World Health Organisation (WHO) guidelines, however, most of them do exceed those of the Institution of Turkish Standards (ITS). Concentrations ranging from 0.02 to 0.17 Bq.l(-1) and from 0.01 to 0.29 Bq.l(-1) for gross-alpha and gross-beta radioactivity, respectively, were observed in all samples. For most of the samples, there were no regular correspondence between gross-alpha and gross-beta activity concentrations.
Keywords: Ra-226